2016
DOI: 10.1002/jmv.24576
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of hepatitis B virus (HBV) in Madagascar

Abstract: Hepatitis B virus (HBV) is a DNA virus belonging to Hepadnaviridae family. Chronic infection with HBV is one major risk factor of hepatic disease. In Madagascar, former studies classified the country as part of high endemic area, as HBV prevalence can reach 23% in general population. However, this prevalence differs largely between urban and rural areas and is estimated to be, respectively, 5% and 26%. The aims of the present study were to describe the genetic diversity of HBV strains from different regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Madagascar is considered a country with a high level endemicity for HBV [25][26][27]35]; inside this country the genotype E is the most prevalent, followed by genotype A1 and D [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Madagascar is considered a country with a high level endemicity for HBV [25][26][27]35]; inside this country the genotype E is the most prevalent, followed by genotype A1 and D [28].…”
Section: Discussionmentioning
confidence: 99%
“…Madagascar is classified as a high endemic area for HBV, and around 5% of the urban population and 30% of the rural population are chronic HBsAg carriers [25][26][27]. A recent study indicated that genotype E is the most prevalent in Madagascar followed by genotype A1 and D [28].…”
Section: Evolutionary Rate Estimation Time-scaled Phylogeny and Population Dynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After a first serological screening searching HBs antigen, total DNA was extracted from positive sera using the NucleoSpin1 Dx Virus (MACHEREY‐NAGEL SARL, a67722 Hoerdt, France), according to the manufacturer's instructions, as previously described [Andriamandimby et al, ]. Sequences of about 1,348 nucleotides were amplified using a previously described multiple nested PCR protocol in order to obtain the HBV polymerase (P) and surface antigen (PreS/S) sequences [Zehender et al, ].…”
Section: Methodsmentioning
confidence: 99%